Accelerated hydration reaction of an unsymmetrical tolan evidenced by a Hg(ii)-trapped macrocycle and its application as a Hg(ii)-selective indicator. Issue 71 (11th August 2016) - Hong, Jung-Ho; Kurapati, Sathish; Jo, Yunhee; Shin, June-Ho; Cho, Dong-Gyu
Abstract : Hg(ii )-mediated hydration reactions of unsymmetrical quinoline type tolans were studied and further used for the detection of Hg(ii ) in buffered media. Abstract : Hg(ii )-mediated hydration reactions of unsymmetrical quinoline type tolans were studied. The observed accelerated reactions of the tolans rely on the additional binding motifs of the tolan, as supported by the X-ray structure of the macrocycle (2b ). The analyte-specific reaction allows us to detect Hg(ii ) in buffered media.